Severity and clinical causes of chronic kidney disease among outpatients from selected hospitals in Nairobi County, Kenya - Mbithi, Annastacia N.; Kimani, Harun M.; Orago, Alloys S. S. (International Journal Of Community Medicine And Public Health, 2021)
Background: Chronic kidney disease (CKD) is a worldwide public health issue with high prevalence (8% and 16%) among adults. The severity of CKD and associated clinical features are less characterized in Kenya. We set to determine severity and clinical features of CKD among outpatient attendees in selected hospitals in Nairobi county. Methods: In this hospital based analytical cross-sectional study design, we collected data from Kenyatta National Hospital (KNH), Aga Khan University Hospital (AKUHN) and Mater Misericordiae Hospital. We recruited 336 adult CKD outpatients aged 18 years and above attending nephrology clinics between January and July, 2020 using a simple random sampling. A self-administered questionnaire was used to collect social-demographic data while data on severity and clinical features were retrieved from patient’s files of those who had given an informed consent. Descriptive and inferential statistics were performed using statistical package of social science version 26.0. Results: Majority of CKD patients (61.9%) had severe disease. Among patients with CKD, the following clinical features were statistically significant with severe disease; diabetic nephropathy (OR 3.43, 95% CI; 1.72, 5.67), glomerulonephritis (OR 2.52, 95% CI; 2.07, 4.05), hypertensive nephrosclerosis (OR 1.95, 95% CI; 1.87, 3.11), polycystic kidney disease (OR 1.26, 95% CI; 1.12, 2.61) and systemic lupus erythematosus (OR 1.16, 95% CI; 1.06, 1.39). Conclusions: Among outpatient attendees in Nairobi county, severe CKD is likely to be found in patients with diabetic nephropathy, glomerulonephritis, hypertensive nephrosclerosis, polycystic kidney disease and systemic lupus erythematosus. Therefore, the patients with these features need proper follow up and treatment to slow down progression of CKD to severe stages. However, more studies are need to be done to ascertain that the clinical features are responsible for severe CKD.